'[Sir, ] Who is the English Authority on Pronunciation?': Accent and Normative Attitude in The Times (1785–1922). (2nd January 2016) - Sturiale, Massimo
Abstract: This paper highlights the role of The Times as a mirror of the Late Modern standard accent ideology and normative tradition. The debate on language standards — which first involved grammarians, lexicographers, and orthoepists —, thanks to the 'new' media, went beyond the scholarly confines, thus allowing 'the lay community' (Lukač2015 : 1) to have their say on linguistic matters. Some of the questions addressed concern the perception of 'authority on pronunciation' in nineteenth-century Britain through the analysis of a corpus of letters to the editor published in the period 1785 to 1922.